Recruitment of neutrophils in glomeruli in early mouse sepsis is associated with E-selectin expression and activation of endothelial NF-κB and MAPK pathways - Zhendong, Wang; Dayang Erna Zulaikha, Awang Hamsin; Peter J., Zwiers; Martha L., Hernandez Garcia; Matthijs, Luxen; Matijs van, Meurs; Jan A.A.M, Kamps; Jill, Moser; Grietje, Molema (Oxford Academic, 2024)
Sepsis is a dysregulated systemic inflammatory response to an infection, which can lead to 18 multiple organ dysfunction syndrome that includes the kidney. Leukocyte recruitment is an 19 important process of the host immune defense in response to sepsis. Endothelial cells (EC) 20 actively regulate leukocyte recruitment by expressing adhesion molecules following the 21 activation of dedicated intracellular signal transduction pathways. Previous studies reported that the expression of adhesion molecules was associated with the activation of endothelial NF-κB 2 p65 and MAPK c-Jun pathways in vitro in response to conditions that mimic processes that occur 3 in inflammation. This study aimed to investigate the spatiotemporal patterns of leukocyte 4 recruitment, expression of adhesion molecules, and endothelial nuclear p65 and c-Jun localization 5 in renal microvascular beds of septic mice. Here, we used a cecal ligation and puncture (CLP) 6 sepsis mouse model and RT-qPCR and immunohistochemical staining. We showed that 7 neutrophils, macrophages, and T lymphocytes were all present in the kidney, yet only neutrophils rnible pattern, mainly in glomeruli at 4 hours after CLP9 sepsis initiation. E-selectin, not VCAM-1, was expressed in glomeruli at the same time point. In a 10 subset of mice at 72 hours after CLP-sepsis started, VCAM-1 expression was prominent in 11 glomerular EC, which was not related to changes in mmu-microRNA(miR)-126a-3p levels, a 12 short noncoding microRNA previously shown to inhibit the translation of VCAM-1 mRNA into 13 protein. Nuclear localization of p65 and c-Jun occurred in EC of all microvascular segments at 4 14 and 7 hours after CLP-sepsis initiation. In summary, sepsis-induced recruitment of neutrophils, 15 E-selectin expression, and NF-κB p65 and MAPK c-Jun pathway activation coincided in 16 glomeruli at the early stage of the disease. In the other microvascular beds, sepsis led to NF-κB 17 p65 and MAPK c-Jun pathway activation with limited expression of E-selectin and no association 18 with VCAM-1 expression or leukocyte recruitment.